Szkolenia i projekty jako metody aktywizacji zawodowej osób bezrobotnych na przykładzie działań Powiatowego Urzędu Pracy w Nowym Sączu - Michalik, Bogumiła (My University, 2013)
Zjawisko bezrobocia oddziałuje negatywnie na wiele aspektów życia, od sytuacji materialnej począwszy, przez kondycję psychiczną bezrobotnych, po ich wykluczenie społeczne, a nawet poziom przestępczości. Szczególnie w dobie kryzysu rząd przeznacza duże środki na aktywną politykę rynku pracy, realizowaną za pośrednictwem Powiatowych Urzędów Pracy. W obszarze badań autorskich znalazł się system aktywizacji zawodowej bezrobotnych w powiecie nowosądeckim. Ich celem była analiza lokalnego rynku pracy i roli, jaką odgrywa na nim PUP. Praca badawcza wykazała, że instytucja ta prawidłowo spełnia swoje ustawowe obowiązki, a jej oferta szkoleniowa dostosowana jest do potrzeb i oczekiwań lokalnego rynku pracy. Ponadto stwierdzono, że długotrwałe bezrobocie jest w większości przypadków wynikiem braku zaangażowania i spójnej wizji wychodzenia z bezrobocia, którą bezrobotny mógłby realizować przy wsparciu PUP.

The phenomenon of unemployment is having an influence negatively on a lot of aspects of life, from financial circumstances having conceived, through the psychological condition of unemployed persons, crime for their social exclusion, not to say the level. Particularly in twenty-four hours of the crisis the government is allocating big funds for the active labour market policy, carried out via district job centres. In the area of research author's a system of the vocational activation of the unemployed was in a Nowy Sącz district. Analysis of the local labour market and the role on it a District Employment Office is acting which was their purpose. The research work showed that this institution correctly was performing its statutory duties, and for her the training offer is adapted to needs and expectations of the local labour market. Above it they stated that the long-term unemployment was a result of the due to a lack of the commitment and the consistent vision of leaving the unemployment which the unemployed person could carry out in most cases at supporting the District Employment Office.
Trainings and projects as the methods of professional activation of the unemployed based onon the example of activities of the District Labour Office in Nowy Sacz
Keywords: aktywizacja zawodowa; bezrobocie; instytucja rynku pracy; polityka rynku pracy; rynek pracy; szkolenie; vocational activation; unemployment; labour market institution; labour market policy; labour market; training